Leadership development through executive coaching process in selected private organisations - Nawab Zadah Khan, Nasreen Khanum (2021)
Executive coaching has emerged in the human capital development practise as an effective development tool in improving leadership skills for leaders to drive organisations towards success and better performance. Despite its effectiveness, the understanding on how coaching works and how the learning process internalised within coaching came into practice remain unclear. The complexity of an executive coaching program is underestimated and not adequately understood. The ambiguity around it influenced the level of adoption among human resource practitioners which create huge loss of opportunity in the leadership development area. This study assessed executive coaching process for leadership development in order to contribute meaningfully in understanding the learning opportunities offered by the process which were supported by four research questions: (1) What is the common structure for an executive coaching program? (2) What are the diverse learning pathways in the executive coaching program? (3) How coachee learns during coaching process? and (4) What are leadership qualities that have been established as a result of the coaching process? The study adopts qualitative methodology guided by a case study approach, which analysed executive coaching program conducted by International Coaching Federation (ICF) coaches as the source of data collection. A total of eight informants participated in this study, consisting of coaches and coachees, who were interviewed on their coaching experiences to understand how the process created effective learning pathways which leads to opportunities for positive changes within coachees. Data were collected through comprehensive, semi-structured interviews, document analysis along with participant and non-participant observation related to the executive coaching program. The data were analysed further by code, categorisation and sub-themes to address the research questions to develop the main theme. Research results indicated that learnings within coaching is a dynamic process that integrates various learning opportunities. Learning happens through conscious meaning making process which connects coachee’s mind and experiences. Deliberate and focused series of powerful questioning during the coaching session facilitates critical reflection in coachee’s learning process to enable shift in coachee’s state of mind, which underpins change in behaviour, actions, thinking, values and expectations. The research indicates that coaching is a relational based approach supported by four important pillars to enhance effectiveness of its process; trust, chemistry, confidentiality and commitment. The trustful relationship between coach and coachee is also an important factor for ensuring successful learning in a coaching phase. This study gave new perspective towards leadership development approach which empowers coachee for their personal growth and self-development. Higher sense of empowerment indicated higher effectiveness in a change process. Main outcome of an executive coaching process is putting a thinking structure within coachee, supported by powerful questioning and reflection. Consistent practise enabled coachee to internalise the learning process and embedded the structure within them, creating sustainable change. This study offers insights on how coaching process change coachee’s behaviours and actions through the development of their states of mind. Adopting the five states of mind framework as part of critical reflection provided more structured thought process to facilitate deep thinking and self-exploration which open up huge growth and development opportunities. The framework developed through this research will benefit various stakeholders including practitioners of human resources, skilled coaches and even coachees in planning and developing effective leadership programmes for optimal strategic development and personal growth.